Adsorption of Heavy Metal Cu(II) in Wastewater Using Adsorbents from Empty Oil Palm Bunches - Fitri, Indah; Nasution, Hafni Indriati; Jasmidi, Jasmidi; Zubir, Moondra; Rahmah, Siti; Selly, Rini; Faradilla, Putri (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Heavy metal pollution has increased with increasing industrialization. To overcome this contamination, carried out by using the adsorption method. The adsorbents used are activated carbon and porous polymer composite carbon Cu(TAC). in liquid waste, one of which is Cu metal. This is evidenced by the existence of data showing the efficiency of activated carbon and porous polymer composite carbon Cu(TAC) above 90%. In addition, activated carbon and porous polymer composite carbon Cu(TAC) have an adsorption isotherm equation that is suitable for Cu(II) adsorption is the Langmuir isotherm with linear regression values of 0.9045 and 0.8912.